Pore structure analysis and properties evaluations of fly ash-based geopolymer foams by chemical foaming method. Issue 16 (November 2018) - Xu, Fang; Gu, Gonghui; Zhang, Wu; Wang, Huiming; Huang, Xiaoming; Zhu, Jing
Abstract: In this paper, a new kind of fly ash-based geopolymer foams was prepared by chemical foaming method. The effects of foaming agent, foam stabilizer and foaming temperature on the dry density, fluidity, compressive strength, thermal conductivity and capillary water absorption of the geopolymer foams were studied. The pore structure parameters of geopolymer foams specimens including porosity, pore size distribution, Feret diameter and average roundness, were obtained by ImagePro plus image analysis software. Moreover, the influence of pore structure parameters on the properties of geopolymer foams was analyzed. The morphology and characteristics of pore structure of the geopolymer foams were also observed by shape measurement laser microscope and scanning electron microscope. The dry densities of geopolymer foams could range from 142 kg/m 3 to 1021 kg/m 3 and the compressive strength could range from 3.2 MPa to 44.81 MPa. The specimens of geopolymer foams possess good pore structure at 3.5% content of H2 O2 and 2.85% content of sodium dodecyl sulfate. The dry density, compressive strength and thermal conductivity have a good correlation with the pore structure parameters of geopolymer foams. From the observation of the microscopic tests, the microstructure of geopolymer foams is loose and porous. Besides, the morphology and size of typical pores could be obtained. The microstructure and morphology characteristics could be well explained the macroscopic properties of the geopolymer foams.